Apatite with lamellae of sulfide and other phases in ultrahigh-pressure eclogites from Nové Dvory, Moldanubian Zone, Czech Republic. (26th July 2018) - Faryad, Shah Wali; Jedlicka, Radim; Perraki, Maria
Abstract: Exsolution lamellae of baryte, Fe sulfides, Cu sulfides and Fe oxides were observed in apatite enclosed in garnet and omphacite and their intergranular spaces in ultrahigh-pressure eclogite in the Moldanubian Zone, Czech Republic. Micro-textural relations and compositional mapping of the apatite indicates a close relationship between the density of the exsolution lamellae and compositional domains that are rich in sulfur and iron. No relation between compositional domains and fluorine or chlorine content or any evidence of apatite metasomatisation was observed. On the basis of cathodoluminescence images, the compositional domains reflect sector zoning in apatite crystals by preferential uptake of elements due to differences in surface charge and morphology on the growth plane. It is concluded that the lamellae are products of exsolution in a closed system resulting from temperature decrease during metamorphism.